Contemporary perspective of spirituality and religiosity in head and neck cancer - Nikunj Maniyar; Sachin C. Sarode; Shruti Thakkar; Gargi S. Sarode (Oral Oncology Reports)
Head and neck cancer (HNC) poses significant challenges, not only in terms of physical health but also in psychosocial and spiritual dimensions. Religiosity and spirituality have emerged as crucial factors in the coping mechanisms of individuals diagnosed with cancer, including HNC. Addressing the spiritual needs, which comprehend existential concerns across various domains, represents a pivotal aspect of cancer care. Purvey of such care has been allied with better psychological and spiritual adaptation, along with reduced utilization of aggressive end-of-life interventions. Research underscores the profound influence of spirituality and religiosity on quality of life (QoL) among HNC patients, emphasizing the imperative of addressing to spiritual needs within the framework of holistic care. Additionally, neglecting the spiritual dimensions may favour suboptimal treatment outcomes and compromised patient adherence. Amidst obstacles such as insufficient training and apprehensions surrounding religious influence, collaborative initiatives involving variety of resources offer a potential avenue for strengthening spiritual support for patients with HNC. In essence, recognizing and addressing patients' spiritual needs constitute integral components of comprehensive care in HNC, nurturing resilience and promoting well-being within the adversities of illness.